2016
DOI: 10.1186/s12984-016-0111-3
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical walking mechanisms underlying the metabolic reduction caused by an autonomous exoskeleton

Abstract: BackgroundAnkle exoskeletons can now reduce the metabolic cost of walking in humans without leg disability, but the biomechanical mechanisms that underlie this augmentation are not fully understood. In this study, we analyze the energetics and lower limb mechanics of human study participants walking with and without an active autonomous ankle exoskeleton previously shown to reduce the metabolic cost of walking.MethodsWe measured the metabolic, kinetic and kinematic effects of wearing a battery powered bilatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
172
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(192 citation statements)
references
References 21 publications
(46 reference statements)
16
172
4
Order By: Relevance
“…This study also provides suggestive evidence that metabolic improvements may stem from not only reductions in muscle activity at the assisted joint, but other joints as well, such as the hip. This finding is consistent with other work in lower-extremity exoskeletons [32].…”
Section: Discussionsupporting
confidence: 83%
“…This study also provides suggestive evidence that metabolic improvements may stem from not only reductions in muscle activity at the assisted joint, but other joints as well, such as the hip. This finding is consistent with other work in lower-extremity exoskeletons [32].…”
Section: Discussionsupporting
confidence: 83%
“…Some full-body exoskeletons have resulted in large metabolic penalties (e.g. [7]) while lightweight ankle-foot exoskeletons have resulted in penalties of less than 3% for active autonomous 1 exoskeletons [4] and even close to zero for passive autonomous1 exoskeletons [5]. Reducing the penalty of wearing an exoskeleton in zero-work mode is mainly a design challenge, while increasing the difference between the zero-work condition and powered exoskeleton conditions is mainly a biomechanics challenge.…”
Section: Introductionmentioning
confidence: 99%
“…They found a convex landscape in metabolic cost versus actuation timing with an optimum around 40% of the stride. Studies that have found the highest reductions in metabolic energy cost have also used an actuation timing around 40% of the stride [4, 6]. …”
Section: Introductionmentioning
confidence: 99%
“…How the musculoskeletal system achieves this has been studied extensively (for good reviews see [1–4]). Contemporary applications of this research include: increasing understanding of neuromuscular disorders [5,6], probing musculoskeletal injury mechanisms [7,8] and providing bio-inspiration for robotic, prosthetic and wearable assistive technologies [914]. It is clear that we need to understand how the human musculoskeletal system generates work for movement, but to date most research has focused on the special case of constant-speed locomotion on level ground (steady-state).…”
Section: Introductionmentioning
confidence: 99%